Kewenagan Direktur sebagai Perwakilan Perusahaan dalam Mendaftarkan Merek Atas Nama Pribadi - Cindy Yolanda; Prisca Oktaviani Samosir (Supremasi Hukum: Jurnal Penelitian Hukum, 2020)
Trademarks as identification and differentiating goods and / or services can be registered by legal subjects of individuals and legal entities. The director runs the company based on his rights and obligations. Then, the director registers the company's trademark by being registered in his personal name. If it can be done, whether the transfer of rights to the brand has moral rights and economic rights can be transferred. This research is to find out whether in a brand regulation a legal entity (company) can register a brand by the director by using a personal name. And whether a brand can be said to be an asset included in the company. The type of research that will be used is normative research using secondary data. The method of data collection uses library research and uses qualitative analysis. The results of the study indicate that the director who registered the brand is one of the founders of the company and registration is done with the first usage system that determines the creation of rights to the brand and registration has been approved by the GMS.Intangible Assets, Director Authority, Brands, Trademark Registration.